(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Power quality is an important issue today. It gains importance especially with the launch of smart devices with very good performance for good energy. Electrical problems refer to the phenomenon of terminal equipment not working properly due to voltage, current or frequency inconsistency. The biggest problem here is power loss. To solve this problem, special power supplies are used. One such device is the Dynamic Voltage Corrector (DVR), which is the most efficient and effective modern voltage corrector used in power distribution systems. Its appeal includes lower cost, smaller size, and faster response to disturbances. This article describes how to develop, simulate and analyze a digital video recorder (DVR) using MATLAB Simulink. To improve the ability to recover from DVR voltage, this article includes the development of a control model that uses a separate PWM pulse generator. The results show that the DVR design can adjust the voltage level under voltage drop conditions..